Boron‐doped hydrogenated silicon carbide alloys containing silicon nanocrystallites for highly efficient nanocrystalline silicon thin‐film solar cells. (26th February 2015) - Lee, Ji Eun; Ahn, Seung Kyu; Park, Joo Hyung; Yoo, Jinsu; Yoon, Kyung Hoon; Kim, Donghwan; Cho, Jun‐Sik
Abstract: Boron‐doped hydrogenated silicon carbide alloys containing silicon nanocrystallites (p‐nc‐SiC:H) were prepared using a plasma‐enhanced chemical vapor deposition system with a mixture of CH4, SiH4, B2 H6 and H2 gases. The influence of hydrogen dilution on the material properties of the p‐nc‐SiC:H films was investigated, and their roles as window layers in hydrogenated nanocrystalline silicon (nc‐Si:H) solar cells were examined. By increasing the RH (H2 /SiH4 ) ratio from 90 to 220, the Si―C bond density in the p‐nc‐SiC:H films increased from 5.20 × 10 19 to 7.07 × 10 19 /cm 3, resulting in a significant increase of the bandgap from 2.09 to 2.23 eV in comparison with the bandgap of 1.95 eV for p‐nc‐Si:H films. For the films deposited at a high RH ratio, the Si nanocrystallites with a size of 3–15 nm were formed in the amorphous SiC:H matrix. The Si nanocrystallites played an important role in the enhancement of vertical charge transport in the p‐nc‐SiC:H films, which was verified by conductive atomic force microscopy measurements. When the p‐nc‐SiC:H films deposited at RH  = 220 were applied in the nc‐Si:H solar cells, a high conversion efficiency of 8.26% (Voc  = 0.53 V, Jsc  = 23.98 mA/cm 2 and FF = 0.65) was obtained compared to 6.36% (Voc  = 0.44 V, Jsc  = 21.90 mA/cm 2 and FF = 0.66) of the solar cells with reference p‐nc‐Si:H films. Further enhancement in the cell performance was achieved using p‐nc‐SiC:H bilayers consisting of highly doped upper layers and low‐level doped bottom layers, which led to the increased conversion efficiency of 9.03%. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Wide bandgap (E04  = 2.23 eV) p‐nc‐SiC:H window layers with enhanced vertical charge transport were successfully prepared using plasma‐enhanced chemical vapor deposition under a high hydrogen dilution condition, which led to the formation of Si nanocrystallites in the amorphous SiC:H matrix. When applied to n‐i‐p nc‐Si:H solar cells, these films significantly enhanced cell performance due to low recombination at the p/i interfaces, decrease of the series resistance and low absorption loss at the short wavelengths.